2020
DOI: 10.1534/genetics.119.302542
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Strong Selection at the Level of Codon Usage Bias in Drosophila melanogaster

Abstract: Codon usage bias (CUB), where certain codons are used more frequently than expected by chance, is a ubiquitous phenomenon and occurs across the tree of life. The dominant paradigm is that the proportion of preferred codons is set by weak selection. While experimental changes in codon usage have at times shown large phenotypic effects in contrast to this paradigm, genome-wide population genetic estimates have supported the weak selection model. Here we use deep genomic population sequencing of two Drosophila me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 77 publications
(103 reference statements)
1
61
0
Order By: Relevance
“…Genome-wide codon bias is driven by weak selective forces, mutation and genetic drift (6). While selection has been demonstrated to play a dominant role of in non-mammalian species (36,51), in mammalian species mutational biases are more prominent (52,53) and the contribution of selection is more disputed (6,22). This correlates well with our findings where the conserved bias in codon use and mRNA secondary structures in M. musculus is less pronounced than in the other four model species.…”
Section: Discussionsupporting
confidence: 88%
“…Genome-wide codon bias is driven by weak selective forces, mutation and genetic drift (6). While selection has been demonstrated to play a dominant role of in non-mammalian species (36,51), in mammalian species mutational biases are more prominent (52,53) and the contribution of selection is more disputed (6,22). This correlates well with our findings where the conserved bias in codon use and mRNA secondary structures in M. musculus is less pronounced than in the other four model species.…”
Section: Discussionsupporting
confidence: 88%
“…Our results may also be influenced by differences between groups in terms of selection on codon usage. It has been shown that in Drosophila synonymous mutations are subject to both weak and strong selection [47,48], which in turn has been shown to potentially lead to an upward bias in the estimation of α [49] (at least when α is estimated as 1…”
Section: Plos Geneticsmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted December 20, 2020. ; https://doi.org/10.1101/2020.12.18.423529 doi: bioRxiv preprint Shah and Gilchrist, 2011;Gilchrist et al, 2015;Landerer et al, 2020;Lawrie et al, 2013;Machado et al, 2020). One particularly powerful population genetics approach is the Ribosomal Overhead Cost Stochastic Evolutionary Model of Protein Production Rates (ROC-SEMPPR), which is able to separate out the effects of mutation and selection on codon usage by accounting for the natural variation in intergenic gene expression (Shah and Gilchrist, 2011;Gilchrist et al, 2015;Wallace et al, 2013).…”
Section: Introductionmentioning
confidence: 99%